GAMBARAN EPIDEMIOLOGI COVID-19 DAN HUBUNGANNYA DENGAN PERILAKU PENCEGAHAN DI KOTA SEMARANG - Nabilah, Zaimatun (Jurnal Kesehatan Masyarakat (Undip), 2022)
The COVID-19 pandemic caused by the SARSCoV-2 virus in 2019 had caused 2 million deaths in 220 countries in the world until March 2021. The city of Semarang is ranked first in Central Java with 72,329 confirmed cases, with sufferers dominated by men (52.6%) and women (47.4%), and the age range mostly suffered by productive age (20-54 years) as many as 1,142 people (52%).Health behavior according to L. Green is influenced by several factors; predisposing, reinforcing, and enabling. The purpose of this study was to determine the faetures of the epidemiology of COVID-19 and its relationship with preventive behavior in the city of Semarang. The type of research is observational analytic and cross sectional design with simple random sampling technique. The research sample is 55 respondents. Data were analyzed by Chi Square statistical test and logistic regression. The results showed that the factors associated with COVID-19 prevention behavior were gender (p<0.05; PR=2.89), level of knowledge (p<0.01; PR=4.57), and attitude of prevention (p<0.05; p<0.05; PR=3.53). After controlling for other variables, the most influential factor on COVID-19 prevention behavior was the level of knowledge (p=0.007). There is a relationship between gender, level of knowledge, and prevention attitudes with COVID-19 prevention behavior, but there is no relationship between age, employment status, education level, role of health services, vaccination status, history of social contact with COVID-19 patients. 19 with COVID-19 preventive behavior. The advice for this research is to always follow the development of information from trusted sources regarding COVID-19 and always obey health protocols.